Volunteerism in the U.S. Armed Forces: An Interpretive Study - Barnes, Michael Dominic (My University, 2025)
The modern United States military is populated by service members who choose to serve voluntarily. The All-Volunteer Force is celebrated in modern America, touted as a cultural achievement in that the nations’ warfighters are altruistic citizens. While individual motivations may vary greatly, many active-duty service members embrace the notion of serving their country as a civic duty. Military service is seen by many as the ultimate form of community service and volunteerism, honored nationally and in local communities. Yet, within the ranks of the US military some service members go beyond voluntary military service, choosing to volunteer locally with community and nonprofit organizations. In a study on volunteerism of OEF/OIF veterans, 70% of survey respondents stated they had volunteered while serving on active duty (Yonkman & Bridgeland, 2009). The benefits of volunteerism are well established in research and literature particularly in studies on veterans, communities, and volunteers in civil society (Usbeck, 2018; Spera, 2015). These studies focus on civilian contexts and experiences of veterans, not those still serving in the armed forces. Why is this important to study? There are many programs and organizations in communities that benefit from veterans who participate, and those veterans in turn benefit from continued service. Can the benefits of volunteerism be turned back towards current service members? Service members gain knowledge, skills, and abilities through military training and experience that are valuable outside of military service. In a review of the literature, studies on the benefits of volunteerism for veterans are well established, especially for successful reintegration into society and countering suicide. Ideally, volunteerism can provide an outlet to practice and adapt leadership and communication skills for transition back to society while normalizing community connections and reducing isolation.
Volunteerism in the U.S. Armed Forces: an interpretive study
Keywords: Volunteerism; Military; Service; Community; Transition